UNCOVERING THE COMPLEXITIES OF PAY FAIRNESS: AN EXPLORATORY STUDY ON THE MEASUREMENT AND NATURE OF PAY FAIRNESS - Kulikowski, Konrad (Organizacja i Kierowanie, 2023)
This study aims to enhance the understanding of pay fairness in workplaces, an essential yet often overlooked aspect of workplace social relations. Using confirmatory factor analysis, we compare seven models of pay fairness inspired by current literature. We propose that pay fairness should not be treated as unidimensional, but as a multidimensional construct. A fourdimensional model of distributive, procedural, interpersonal, and informational pay fairness may be preferred in theory and compensation practice. Results suggest that four pay fairness dimensions might have distinct roles in predicting employee work functioning, confirming the complex nature of employees’ pay fairness perception.